Dark Energy Survey identification of a low-mass active galactic nucleus at redshift 0.823 from optical variability. Issue 3 (23rd June 2020) - Guo, Hengxiao; Burke, Colin J; Liu, Xin; Phadke, Kedar A; Zhang, Kaiwen; Chen, Yu-Ching; Gruendl, Robert A; Lidman, Christopher; Shen, Yue; Morganson, Eric; Aguena, Michel; Allam, Sahar; et al.
ABSTRACT: We report the identification of a low-mass active galactic nucleus (AGN), DES J0218−0430, in a redshift z = 0.823 galaxy in the Dark Energy Survey (DES) Supernova field. We select DES J0218−0430 as an AGN candidate by characterizing its long-term optical variability alone based on DES optical broad-band light curves spanning over 6 yr. An archival optical spectrum from the fourth phase of the Sloan Digital Sky Survey shows both broad Mg ii and broad H β lines, confirming its nature as a broad-line AGN. Archival XMM–Newton X-ray observations suggest an intrinsic hard X-ray luminosity of L_2-12 keV≈ 7.6± 0.4× 10^43 erg s −1, which exceeds those of the most X-ray luminous starburst galaxies, in support of an AGN driving the optical variability. Based on the broad H β from SDSS spectrum, we estimate a virial black hole (BH) mass of M ≈ 10 6.43 –10 6.72 M⊙ (with the error denoting the systematic uncertainty from different calibrations), consistent with the estimation from OzDES, making it the lowest mass AGN with redshift > 0.4 detected in optical. We estimate the host galaxy stellar mass to be M * ≈ 10 10.5 ± 0.3 M⊙ based on modelling the multiwavelength spectral energy distribution. DES J0218−0430 extends the M – M * relation observed in luminous AGNs at z ∼ 1 to masses lower than being probed by previous work. Our work demonstrates the feasibility of using optical variability to identify low-mass AGNs at higher redshift in deeper synoptic surveys with direct implications for the upcoming Legacy Survey of Space and Time at Vera C. Rubin Observatory.